Non operative treatment of chronic ankle sprain: a study conducted in teaching general hospital, Telangana, India - Mattam, Sanjay; KR, Panduranga Rao; Reddy, Chinthaparthi Mallikarjuna (International Journal of Research in Medical Sciences, 2017)
Background: Chronic ankle sprain due to “sprained ankle syndrome” may be particularly troublesome. Some causes of chronic ankle instability may be symptomatic insufficiency of pathologic laxity, arthro-kinematic changes, degenerative changes, decrease of proprioception and inadequate neuromuscular control. This study was conducted to review our experience with footwear correction of chronic ankle sprains of grade 2 and 3. Methods: Ankles of 280 patients, who had chronic ankle sprains grade 2, grade 3 were considered in this study, to assess results of non-operate treatment. Diagnosis was made with history of pain, swelling on walking, clinical findings of swelling, tenderness on antero-lateral aspect of lateral malleolus. All patients were given 3 days of anti-inflammatories, analgesics and footwear modifications. Later patients were advised exercise program. Results: Out of 280 patients, who were regularly followed, 92% people had relief, 3.4% of patients continued footwear as they had associated symptoms, 3.9% of patient continued to have pain maybe obscure or not following doctor orders. Conclusion: The study concludes that lateral elevated foot wear made of micro cellular rubber of 0.75 cm is the choice of treatment for grade 2 and 3 ankle sprains. This foot wear helps in biomechanical correction from varus and also decreases symptoms and signs. Cosmetically acceptable.